Influencing Factors for the Quality of Homework Assignments - Lamichhane, Purna Bahadur (Cognition, 2024)
This research article endeavors to explore teachers’ perspectives on effective homework practices and the standards for assigning high-quality homework tasks. Using a qualitative research approach within interpretive paradigms, the study conducted interviews with experienced school teachers through convenience sampling. The investigation delves into strategies for customizing homework to meet students’ needs, the role of parental engagement, and the importance of balancing the quantity and quality of homework assignments. Although homework serves as a vital tool in reinforcing learning and enhancing academic skills beyond classroom hours, various challenges hinder its completion, including comprehension gaps and issues with time management and parental involvement. The study seeks to uncover educators’ insights into the types of homework anticipated by students and the factors shaping effective homework practices. The findings emphasize the need to balance parental involvement to promote children’s independence and responsibility, avoiding excessive assistance that may undermine the intrinsic value of homework. Moreover, the study advocates for prioritizing homework quality over quantity to mitigate negative impacts on student well-being, emphasizing meaningful learning experiences and considering diverse preferences when designing assignments.